(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To investigate the effectiveness of dyslipidemia treatment in patients with type 2 diabetes at An Phuc General Clinic. Subjects and methods: Prospective cohort study, describing 172 patients diagnosed and treated for type 2 diabetes with primary dyslipidemia at An Phuc General Clinic, from February 2021 to October 2021. Results: The majority of patients were treated with Statins of 67.44%. Then the fibrates group accounted for 24.42%. The resin group was used the least with 12.21%. Most patients treated for dyslipidemia with 1 drug, accounting for 55.81%, mainly statin drugs. The rate of patients experiencing side effects was 36.63%. The percentage of patients who did not reach the goal of treatment for dyslipidemia was still quite high at 37.21%. There was a correlation between reaching the treatment goal and the age group with statistical significance (p<0.05). There was no statistically significant relationship between gender, education level and reaching the treatment goal (p>0.05). There was no statistically significant relationship between achieving the goal of blood lipid treatment and achieving the goal of diabetes treatment (p>0.05). Conclusion: The majority of patients were treated with statins. The rate of patients experiencing side effects and the percentage of patients not reaching the goal of dyslipidemia treatment were still high. There was a relationship between reaching the treatment goal and the age group. There was no relationship between gender, education level and treatment goal achievement. There was no relationship between the achievement of the goal of blood lipid treatment and the achievement of the goal of diabetes treatment.